Analisis Sejarah Dakwah Syaikh Rifa’i dalam Memperkuat Nilai-Nilai Islam Kultural di Kedungsari Tuwiri Wetan Merakurak - Nikmatul Asiyah; Bella Aulia Ali Kurniawati; Nurul Hakim (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The research aims to analyze the history of Syaikh Rifa’i’s da'wah in strengthening the cultural Islamic values of the community in Kedungsari Tuwiri Wetan, Merakurak, Tuban Regency. This research uses a qualitative approach with a historical research design. Data were obtained through interviews with community leaders, the caretaker of Syaikh Rifa’i’s tomb, and residents, as well as through observation and documentation. The data were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing, while the validity of the data was ensured through source and method triangulation. The results of the study show that Syaikh Rifa’i’s da'wah was carried out through social and cultural approaches that adapted to the conditions of the local community. This approach did not eliminate local traditions but integrated Islamic values into the cultural practices of the community. This process of da'wah formed various cultural Islamic values, such as religiosity, togetherness, cooperation, tolerance, and good morals within the community. These values continue to be passed down through religious traditions such as pengajian, tahlilan, and pilgrimage to the tomb. Therefore, the history of Syaikh Rifa’i’s da'wah plays an important role in strengthening a cultural Islamic identity that is religious, harmonious, and aligned with the local wisdom of the Kedungsari Tuwiri Wetan Merakurak community. Keywords: History of da'wah, Syaikh Rifa’i, Cultural Islam, Kedungsari Community, Local Wisdom